The Molecular Assembly State of Drp1 Controls its Association With the Mitochondrial Recruitment Receptors Mff and MIEF1/2 - Rong Yu (Frontiers Media S.A., 2021)
Drp1 is a central player in mitochondrial fission and is recruited to mitochondria by Mff and MIEFs (MIEF1 and MIEF2), but little is known about how its assembly state affects Drp1 mitochondrial recruitment and fission. Here, we used in vivo chemical crosslinking to explore the self-assembly state of Drp1 and how it regulates the association of Drp1 with MIEFs and Mff. We show that in intact mammalian cells Drp1 exists as a mixture of multiple self-assembly forms ranging from the minimal, probably tetrameric, self-assembly subunit to several higher order oligomers. Precluding mitochondria-bound Drp1 in Mff/MIEF1/2-deficient cells does not affect the oligomerization state of Drp1, while conversely forced recruitment of Drp1 to mitochondria by MIEFs or Mff facilitates Drp1 oligomerization. Mff preferentially binds to higher order oligomers of Drp1, whereas MIEFs bind to a wider-range of Drp1 assembly subunits, including both lower and higher oligomeric states. Mff only recruits active forms of Drp1, while MIEFs are less selective and recruit both active and inactive Drp1 as well as oligomerization- or GTPase-deficient Drp1 mutants to mitochondria. Moreover, all the fission-incompetent Drp1 mutants tested (except the monomeric mutant K668E) affect Drp1-driven mitochondrial dynamics via incorporation of the mutants into the native oligomers to form function-deficient Drp1 assemblies. We here confirm that MIEFs also serve as a platform facilitating the binding of Drp1 to Mff and loss of MIEFs severely impairs the interaction between Drp1 and Mff. Collectively, our findings suggest that Mff and MIEFs respond differently to the molecular assembly state of Drp1 and that the extent of Drp1 oligomerization regulates mitochondrial dynamics.